2017
DOI: 10.1177/0013916517709043
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Local Sea Level Rise Risk Perceptions and the Power of Maps to Change Them: The Effects of Distance and Doubt

Abstract: Audiences that view sea level rise as a distant hazard or hold doubtful or dismissive beliefs about climate change in general may not be receptive to information about this hazard. This study explores how maps may address these challenges to sea level rise communication by making visible the impacts of sea level rise on local communities. Using an interactive map of sea level rise in Sarasota, Florida and an accompanying online survey, it considers how college students from nearby and far away from Sarasota, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 59 publications
0
25
1
Order By: Relevance
“…4 Maps that highlight sea level rise and its effects on coastal communities in the U.S. may be an effective way to shift risk perceptions and beliefs. Retchless (2017) found that exposure to a map highlighting the local impacts of coastal flooding in Florida 4 Leiserowitz further explains, "few Americans associate global warming with extreme events, such as heat waves, hurricanes, flood or drought, despite the fact that all are projected to increase in severity due to climate change" (p. 14).…”
Section: Visual Imagery and Climate Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Maps that highlight sea level rise and its effects on coastal communities in the U.S. may be an effective way to shift risk perceptions and beliefs. Retchless (2017) found that exposure to a map highlighting the local impacts of coastal flooding in Florida 4 Leiserowitz further explains, "few Americans associate global warming with extreme events, such as heat waves, hurricanes, flood or drought, despite the fact that all are projected to increase in severity due to climate change" (p. 14).…”
Section: Visual Imagery and Climate Beliefsmentioning
confidence: 99%
“…Retchless (2017) states, "Although interactive sea level rise maps are one of the more popular means of depicting detailed and local sea level rise impacts, their potential for engaging audiences remains largely unevaluated" (p.6).…”
mentioning
confidence: 99%
“…The choice of elevation model for an assessment study can also have a substantial effect on results owing to combined uncertainties of input datasets, especially elevation and population distribution (Lichter et al, 2011;Mondal and Tatem, 2012;Wolff et al, 2016). The result of many SLR assessments is a set of maps that spatially show the areas exposed to inundation or other adverse effects of specific scenarios of sea-level change, and such maps are enhanced by including a description of mapping uncertainty (Kostelnick et al, 2013;Retchless, 2018), often expressed as a confidence level.…”
Section: Introductionmentioning
confidence: 99%
“…Third, our results inform flood risk perception research and management by directly assessing the influence of digital, interactive flood hazard maps on the spatial flood hazard awareness of coastal residents. Only one previous study has used a similar pre-post study design and found that viewing multimedia, interactive flood risk scenarios was associated with increased flood risk perceptions related to sea level rise among college students in Sarasota, Florida (Retchless, 2018). In contrast, we compared the impact of interactively viewing two flood hazard maps: (a) FEMA's official map of Special Flood Hazard Areas, which is used in current risk management by federal and state agencies and insurance programs but does not depict estimated flood depth and provides little spatial differentiation in flood-prone areas, and (b) a more spatially refined FloodRISE map depicting flood-prone areas by potential flood depth at the street-level scale.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have examined the impact of risk map format, design, and delivery (Fuchs, Spachinger, Dorner, Rochman, & Serrhini, 2009; Hagemeier-Klose & Wagner, 2009; Kjellgren, 2013; Retchless, 2014), only two previous studies have directly assessed the influence of flood hazard maps on flood risk awareness. An early assessment by Handmer (1980) found that hazard maps were ineffective in influencing the public’s perception of flood risk (Handmer, 1980), but a recent study by Retchless (2018) found that college students who viewed an interactive map of sea level rise increased their risk perceptions (Retchless, 2018).…”
Section: Introductionmentioning
confidence: 99%